1984
DOI: 10.1073/pnas.81.2.607
|View full text |Cite
|
Sign up to set email alerts
|

Competitive inhibition by diacylglycerol of specific phorbol ester binding.

Abstract: Emerging evidence suggests that the phorbol ester receptor in brain may be the same as the Ca2+-phospholipid-dependent protein kinase (protein kinase C). Since protein kinase C activity is stimulated by unsaturated diacylglycerol and the phorbol esters can substitute for diacylglycerol in this stimulation, we have examined the effect of diacylglycerols on phorbol ester binding. Assays were carried out with the mouse brain cytosolic phorbol ester aporeceptor, which requires phospholipids for activity. In the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
127
2

Year Published

1985
1985
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 254 publications
(138 citation statements)
references
References 30 publications
8
127
2
Order By: Relevance
“…Studies have shown that PMA substitute its binding to PKC by increasing the affinity of PKC to Ca 2+ and phosphatidylserine, thereby causing the translocation of PKC from cytosol to plasma membrane and its activation (Nishizuka, 1984;Sharkey et al, 1984 DOI:http://dx.doi.org/10.7314/APJCP.2012.13.4.1177 the membrane to activate PKC may inhibit its activity. Pentacyclic triterpenes are structurally similar to sterols and interaction with the cell membrane is thought to be the molecular mechanism underlying their biological effects.…”
Section: 1177 Suppressive Effect Of Maslinic Acid On Pma-induced Promentioning
confidence: 99%
“…Studies have shown that PMA substitute its binding to PKC by increasing the affinity of PKC to Ca 2+ and phosphatidylserine, thereby causing the translocation of PKC from cytosol to plasma membrane and its activation (Nishizuka, 1984;Sharkey et al, 1984 DOI:http://dx.doi.org/10.7314/APJCP.2012.13.4.1177 the membrane to activate PKC may inhibit its activity. Pentacyclic triterpenes are structurally similar to sterols and interaction with the cell membrane is thought to be the molecular mechanism underlying their biological effects.…”
Section: 1177 Suppressive Effect Of Maslinic Acid On Pma-induced Promentioning
confidence: 99%
“…TPA is a stable diacylglycerol analog that mimics the effects of diacylglycerol and strongly activates PKC (43)(44)(45) and is a potent inducer of keratinocyte differentiation (46). Treating cultured keratinocytes with TPA increases cell differentiation, and this change is correlated with an increase in hINV mRNA and protein (7,9,47,48).…”
Section: Involucrin Promoter Activity and Endogenous Hinv Genementioning
confidence: 99%
“…i) Dual regulation of gap junctional communication by cAMP-dependent and Cat+/phospholipid dependent protein kinases Tumor promoters of the phorbol ester family have been shown to bind to and directly activate Ca2+/phospholipid-dependent kinase (protein kinase C) which is activated by diacylglycerols in the presence of phospholipid and physiological concentrations of Ca2+ [7]. Recent studies have shown that homogeneous preparations of protein kinase C from rat brain bind to [3H]-phorbol-12,13-dibutyrate [30] and that diacylglycerols compete with this radioactive ligand for common binding sites [50]. Moreover, diacylglycerol has been shown to exert stimulation on DNA synthesis [49], induction of differentiation of HL-60 cells [36], and inhibition of intercellular communication [15,19], which are also induced by phorbol ester tumor promoters.…”
Section: Regulation Of Cell Communication and Cell Growthmentioning
confidence: 99%